Dietary Supplementation of Limosilactobacillus mucosae LM1 Enhances Immune Functions and Modulates Gut Microbiota Without Affecting the Growth Performance of Growing Pigs - Zhang, Qianqian; Vasquez, Robie; Yoo, Jeong Min; Kim, Sang Hoon; Kang, Dae-Kyung; Kim, In Ho (Frontiers in Veterinary Science, 2022)
Limosilactobacillus mucosae LM1 (LM1) has been isolated from the fresh feces of piglets, but its potential as a direct-fed microbial has not yet been assessed in growing pigs. In this study, we analyzed the probiotic effect of LM1 on the growth performance, apparent total tract digestibility (ATTD) of nutrients, immune properties, intestinal morphology, and colonic microbiota and their metabolites in growing pigs. The experiment included 145 Duroc × (Landrace × Yorkshire) pigs (average body weight: 21.21 ± 1.14 kg) distributed into 5 treatment groups (29 pigs/ treatment) with 6 repetition pens. The pigs were fed either a control diet, or the control diet supplemented with incremental doses of LM1, namely 0.01%, 0.05%, 0.1%, and 0.25%, for 42 d. On d 42, 12 pigs from each of the control and 0.1% LM1 groups were slaughtered. The results indicate that the growth performance and backfat thickness of the pigs are not affected by dietary LM1 levels (P > 0.05). However, the ATTD of nitrogen (N, P = 0.038) improved with LM1 supplementation. Serum pro-inflammatory cytokines, such as interleukin-1β and tumor necrosis factor-alpha, reduced (P < 0.01), while anti-inflammatory cytokine interleukin-10 increased (P < 0.01) with the increasing dose of LM1. The 0.1% LM1-treated pigs exhibited a higher jejunal villus height (VH), greater ileal villus height: crypt depth ratio (V/C) in the ileum (P < 0.05), and a tendency of lower thiobarbituric acid reactant concentration (P = 0.065) in the ileal mucosa compared with the CON pigs. Additionally, dietary supplementation of 0.1% LM1 lowered the alpha diversity (P < 0.05), while boosting (P < 0.05) the populations of Firmicutes and reducing (P < 0.05) the abundance of Bacteroidetes. It also enriched short-chain fatty acid-producing taxa, such as Lactobacillus and Ruminococcaceae, which correlated positively with the increased digesta levels of butyrate and isovalerate. In conclusion, dietary supplementation of increasing levels of LM1 enhanced immune function and improved the ATTD of N without affecting the growth performance of pigs. Additionally, the dietary 0.1% LM1 improved jejunal VH and altered the gut microbial community, as well as the concentrations of butyrate and isovalerate in the colon.